2015
DOI: 10.1002/pd.4753
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of novel fetal echocardiographic morphometric measures of the aortic arch in the diagnosis of neonatal coarctation of the aorta

Abstract: Fetal LCSA, AAo-DAo angle, and TAo-DAo angles are novel measures that can differentiate between subjects with and without CoA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 21 publications
3
63
3
1
Order By: Relevance
“…Our study showed that fetuses with postnatally confirmed CoA exhibited significantly smaller left cardiac structures and diameters of the isthmic region normalized for gestational age. The best Z-scores for prediction of postnatal CoA were those of the MV-annulus, ascending aorta, and isthmus aortae in the sagittal or 3VT views, which have been described in other studies [6,[20][21][22][23][24]. Most studies to date have used Z-scores from Pasquini et al for isthmic or ductal diameters and Schneider et al for intracardiac structures or the ascending aorta, often with a pre-defined cut-off point of < −2 [15,16].…”
Section: Z-scoressupporting
confidence: 70%
“…Our study showed that fetuses with postnatally confirmed CoA exhibited significantly smaller left cardiac structures and diameters of the isthmic region normalized for gestational age. The best Z-scores for prediction of postnatal CoA were those of the MV-annulus, ascending aorta, and isthmus aortae in the sagittal or 3VT views, which have been described in other studies [6,[20][21][22][23][24]. Most studies to date have used Z-scores from Pasquini et al for isthmic or ductal diameters and Schneider et al for intracardiac structures or the ascending aorta, often with a pre-defined cut-off point of < −2 [15,16].…”
Section: Z-scoressupporting
confidence: 70%
“…Similarly, only 1 study had more control fetuses (n = 285) than ours (n = 200). The only measurements from their review that overlapped with our data were the RV/LV end-diastolic diameter ratio reported by Mărginean et al [24] in 2015 and Arya et al [25] in 2016, and the RV/LV end-diastolic area ratio reported by Toole et al [26] in 2015 and Arya et al [25]. Our analysis demonstrated that these ratios were present in 70-84% of fetuses with CoA compared to 5% of the control fetuses, and had the strongest associations compared to the other global and ventricular markers evaluated.…”
Section: Discussionmentioning
confidence: 49%
“…The central axis of the lumen of the fetal DA, where the blood flow is fastest, is not included in the 3VT view where the classic 'V-like' sign is formed by the pulmonary artery and the aortic arch, and the DA seen from the 3VT view is actually the upper part of the fetal DA lumen. Furthermore, physiologically, the angle between the DA and the descending aorta (DAO, 98.4±12.5˚) is significantly larger than that between the aortic arch and the DAO (88.5±5.5˚) (18)(19)(20). Since the 3VT view is obtained in the horizontal direction of the fetal body, the angle between the DA and DAO is relatively large, thereby reducing the probability of forming the smallest angle between the DA and the ultrasound beam compared with that including the aortic arch.…”
Section: Discussionmentioning
confidence: 99%